PENGEMBANGAN MEDIA EDUKASI PARIWISATA MELALUI POS MONOPOLI DALAM UPAYA MENINGKATAN PENGETAHUAN PADA SISWA SMKN 3 KOMODO, LABUAN BAJO - Damianus Sonny Lamoren; I Wayan Adi Putra Ariawan; Farida Ana Mooy (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
This study aims to develop tourism education media based on the Monopoly Post game and to analyze its effectiveness in improving students' knowledge at SMKN 3 Komodo in Labuan Bajo. This research uses a Research and Development (R&D) approach, which includes the stages of needs analysis, product design, development, expert validation, limited trials, and field trials. The research instruments included expert-validation questionnaires, observation sheets, and pretests and posttests to measure improvements in students' knowledge. The results of the study show that the Monopoly Post media developed has a very high level of feasibility, based on assessments by material and media experts, with an average feasibility score above 4.7, placing it in the category of very suitable for use as a learning medium. In addition, the trial results among students showed a significant increase in tourism knowledge. The students' average pre-test score of 64.5 increased to 87.4 on the post-test, a gain of 22.9 points, or approximately 35.9%. This shows that the Monopoly Post media is effective at increasing students' understanding of basic tourism concepts, destination potential, and elements of the tourism industry. In addition to cognitive enhancement, this media has been shown to increase participation, motivation to learn, and interaction among students during the learning process. Game-based approaches provide a more interactive, contextual, and enjoyable learning experience. Thus, the Pos Monopoli educational media can be an effective and relevant learning innovation in supporting the improvement of the quality of tourism education at the vocational high school level.